The Development of Strategic Alliances on the Supply Chain of Apple Agroindustry - Santoso, Imam (Fakultas Teknologi Pertanian Universitas Brawijaya, 2009)
Strategic alliances in supply chain, indeed, play a crucial factor supporting the succesfull of agroindustrial development. Â The development of strategic alliances in apple agroindustry will be further explained in this paper. Â The aims of this research were to identify the factorâs importance level that influenced the establisment of alliances, as well as to formulate the strategic priority to develop the strategic alliances on the supply chain of apple agroindustry.Â Non numeric fuzzy and analythical hierarchy process (AHP) were used to analyze the data. Â Farmers, big sellers, retails, agroindustries, and distributors were involved in developing the supply chain of apple agroindustry. Â The research results showed that the importance level of all factors were quite important for those actors, and relatively higher for that of the agorindustry compared to other actors. Â The developemnt of the apple agroindustryâs supply chain was primary focused on the needs of long term commitment (0.49) in order to increase the volume and value of sales in the supply chain. Furthermore, the selected strategies were improving the marketing performance (37.8%), strengthening the capital of all actors (0.27%), and implementing both the system and technology in effective and effecient way (0.16).Keywords: apple agroindustry, strategic alliances, supply chain